Trematode Cercariae from Lymnaea gedrosiana in the Caspian Sea Littoral in Iran: a one health concern - Eslahi, Aida Vafae; Aligolzadeh, Armin; Pirestani, Majid; Gharibi, Zahra; Abdoli, Amir; Hatam-Nahavandi, Kareem; Bijani, Behzad; Badri, Milad; Ketzis, Jennifer K. (Frontiers in Microbiology, 2023)
Lymnaea gedrosiana snails are hosts to a variety of trematode cercaria of public and veterinary health importance. In Guilan Province, Iran, a region with a high level of fish and bird farming and wetlands important for migratory birds, little is known about the trematode cercaria from L. gedrosiana. From April 2020 to October 2021, six freshwater sites in Guilan Province were sampled for Lymnaeidae snails three times per season (spring, summer, autumn and winter). Snails were exposed to light and heat to induce cercaria shedding and shedded cercaria were identified morphologically and molecularly. In total, 5,712 Lymnaeidae snails were collected of which 3,288 (57.6%) were identified to be L. gedrosiana with 54.3% containing trematode cercaria. Snail and cercaria recovery were This is a provisional file, not the final typeset article highest in the spring and summer. Trematode cercaria identified included Telorchis assula, Hypoderaeum conoideum, Apharyngostrigea pipientis, Sanguinicola cf. inermis, Opisthioglyphe ranae, Diplostomum pseudospathaceum, and Australapatemon burti. The four trematodes D. pseudospathaceum, S. inermis, A. burti, and A. pipientis have not been previously reported in Iran; all four of these can infect migratory birds. The most common cercaria found, H. conoideum (18.3% of the snails) is of zoonotic importance. The third most common cercaria found, S. inermis (10.0% of the snails) is detrimental to fish production. Given the importance of the wetlands in the region for wildlife and migratory birds as well as the number of fish and bird farms in the area, efforts to control L. gedrosiana snails are needed to protect wildlife and human health. In addition, monitoring programs should be implemented to identify and prevent introductions of new trematode species.